Aplicación de los procedimientos policiales frente a la violencia intrafamiliar contra la mujer en el contexto urbano y rural - Paguay Becerra, Nelson Ricardo (2022)
Intrafamily Violence is a social phenomenon with different structural causes, this type of violence is considered any action or omission that consists of physical, psychological or sexual abuse, carried out by a family member against the woman or other members of the family. the same; It is necessary to know the problem from the territory, how violence develops in the family environment, what type of violence predominates in each sector and what are its greatest effects in the short, medium and long term. The present investigation through an exploratory study aims to know the work carried out by the National Police of Ecuador, from the preventive and investigative service, against Domestic Violence in the urban and rural context; In what corresponds to the institution, it is necessary to establish all the legal regulations that allow standardizing the procedures, as well as what is their scope and the limitations that the institution has internally and externally, situations such as: training, logistical, human and institutional coordination. Institution in charge of ensuring the safety of citizens throughout Ecuadorian territory, in the event of Domestic Violence, is the one who initiates the procedure, but other State institutions must be involved in the process, such as: State Attorney General's Office, Council of the Judiciary, the Ministry of Social Inclusion, the Interior, Political Tenures, among others, due to their importance, active participation and involvement is necessary, without them these procedures would not fulfill the objective set forth in Public Policies, such as protecting and guaranteeing the rights of every citizen and in this case of the family and the most vulnerable people.